Content of phenolic compounds and antioxidant capacity in fruits of apricot genotypes - Sochor, Jiri; Zitka, Ondrej; Skutkova, Helena; Pavlik, Dusan; Babula, Petr; Krska, Boris; Horna, Ales; Adam, Vojtech; Provaznik, Ivo; Kizek, Rene (Molecules (Basel, Switzerland), 2010)
Research on natural compounds is increasingly focused on their effects on human health. In this study, we were interested in the evaluation of nutritional value expressed as content of total phenolic compounds and antioxidant capacity of new apricot (Prunus armeniaca L.) genotypes resistant against Plum pox virus (PPV) cultivated on Department of Fruit Growing of Mendel University in Brno. Fruits of twenty one apricot genotypes were collected at the onset of consumption ripeness. Antioxidant capacities of the genotypes were determined spectrometrically using DPPH• (1,1-diphenyl-2-picryl-hydrazyl free radicals) scavenging test, TEAC (Trolox Equivalent Antioxidant Capacity), and FRAP (Ferric Reducing Antioxidant Power)methods. The highest antioxidant capacities were determined in the genotypes LE-3228 and LE-2527, the lowest ones in the LE-985 and LE-994 genotypes. Moreover, close correlation (r = 0.964) was determined between the TEAC and DPPH assays. Based on the antioxidant capacity and total polyphenols content, a clump analysis dendrogram of the monitored apricot genotypes was constructed. In addition, we optimized high performance liquid chromatography coupled with tandem electrochemical and spectrometric detection and determined phenolic profile consisting of the following fifteen phenolic compounds: gallic acid, 4-aminobenzoic acid, chlorogenic acid, ferulic acid, caffeic acid, procatechin, salicylic acid, p-coumaric acid, the flavonols quercetin and quercitrin, the flavonol glycoside rutin, resveratrol, vanillin, and the isomers epicatechin, (-)- and (+)- catechin.
Keywords: Agriculture; antioxidancia; slivoň; Genotype; polyfenoly; Chemistry Techniques, Analytical; fenoly; Prunus; zemědělství; oxidace-redukce; ovoce; chemické techniky analytické; flavonoidy; Antioxidants; Free Radical Scavengers; genotyp; Flavonoids; Phenols; Fruit; Oxidation-Reduction; scavengery volných radikálů; Polyphenols